CPB 1. Development of Drought Screening Protocol for /maize Inbred Lines using Nutrient Culture Technique (The Philippine Journal of Crop Science, 2018)
Water deficit due to climate change is becoming the most important abiotic stress affecting agricultural crops worldwide. Maize is second to wheat in terms of area harvested and first in terms of total production in the world (FAO, 2016). Its high yield potential per unit land area is threatened by drought, intense heat, and dry spell occurrence during the growing period. Process in selecting elite maize inbred lines with potential to be drought tolerant will help in the development of new drought resistant varieties. One way to identify potential drought tolerant maize inbreds is through rapid screening using nutrient culture technique under greenhouse condition. Different combination of nutrient concentration and two known IPB maize inbred lines were used to develop screening protocol for the maize inbred lines. During the initial development of drought screening protocol various drought simulating chemicals were used such as sorbitol, mannitol and PEG added to SNAP™ solution. The addition of mannitol to SNAP™ solution was observed to better simulate drought condition among the chemicals used. This was observed in the more noticeable stunted growth and leaf rolling of maize grown in this solution. Afterwards, different concentrations of mannitol were added to SNAP™ solution to identify the particular concentration that will better simulate drought condition. Addition of 0.075M of mannitol to SNAP™ solution was observed to have significantly reduced most of the growth parameters in both inbred lines. This result is the preliminary finding of the experiment and currently, additional trial is being conducted to further optimize the drought screening protocol which will be further used to screen CIMMYT maize inbred lines.